Atypical Fibroxanthoma: Outcomes from a Large Single Institution Series - Erin McClure BS; Michael J Carr MD, MS; Ayushi Patel BS; Syed Mahrukh Hussnain Naqvi MD, MPH; Youngchul Kim PhD; Michael Harrington MD; Wayne Cruse MD; Ricardo J Gonzalez MD; Vernon K Sondak MD; Amod A Sarnaik MD; Jane L Messina MD; Jonathan S Zager MD (Cancer Control, 2023)
Background Atypical fibroxanthomas (AFX) are rare malignant cutaneous neoplasms. Unfortunately, limited clinicopathologic and outcomes data on this cancer exists. Objective We report the clinical, pathologic, and treatment characteristics, as well as oncologic outcomes in this single-institution retrospective analysis. Methods This retrospective cohort study compiled clinical, pathologic, treatment, and outcome data for all patients with AFX on definitive excision diagnosed, evaluated, and treated primarily by surgical resection at a single institution between 2000-2020. Descriptive statistics evaluated clinical and pathologic characteristics. Kaplan-Meier method and Cox proportional-hazards models were used to evaluate overall survival and recurrence-free survival. Results 78 patients with AFX were identified. The majority were elderly, immunocompetent, Caucasian men. 85% of tumors were located on the head and neck. 63% of patients were correctly diagnosed only after complete resection of the index lesion. The median surgical margin was 1.0 cm. Overall, only 1.3% (1/78) of patients developed a local recurrence (RFS). No patients died of disease. Conclusion This study suggests that resection margins of 1 cm achieve excellent local control with close to 99% RFS and 100% disease-specific survival.